Assessment of Organochlorine Pesticide Residues and Associated Health Risks in Some Vegetables Consumed in Yola, Adamawa State, Nigeria - Umaru, Hauwa Aduwamai; Abubakar, Mohammed; Stephen, Hyelda (African Journal of Biochemistry and Molecular Biology Research, 2024)
The use of pesticides in agriculture can lead to the accumulation of residues in food commodities, posing potential health risks. The levels of organochlorine pesticide residues in selected vegetables (sorrel, spinach, okra, lettuce and sesame) consumed in Yola, Adamawa State, Nigeria were assessed. Vegetable samples were collected, extracted using the QuEChERS method and analysed by gas chromatography-mass spectrometry (GC-MS). Health risk assessment was conducted by estimating the estimated daily intake (EDI), hazard quotient (HQ), hazard index (HI) and lifetime cancer risk (LCR). Organochlorine pesticides, including lindane, aldrin, endosulfan and DDT, were detected in varying concentrations across vegetable samples. Spinach exhibited the highest levels, exceeding European Union Maximum Residue Levels for α-lindane (1.555 mg/kg), β-lindane (1.718 mg/kg), δ-lindane (1.556 mg/kg), aldrin (1.990 mg/kg), endosulfan I (1.960 mg/kg) and endosulfan II (5.209 mg/kg). The HI was 5.56, indicating potential non-carcinogenic health risks. Spinach posed a high cancer risk for α-lindane, β-lindane and p,p'-DDT. Organochlorine pesticide residues in vegetables consumed in Yola exceeded regulatory limits, with spinach posing the highest health risks. Effective monitoring, sustainable agricultural practices and strengthened regulatory frameworks are crucial to safeguard food safety and public health. Thus, consumption of vegetables in Yola should be done with caution.